2018
DOI: 10.1021/acs.molpharmaceut.8b00115
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation and Performance Optimization Based on Microconformational Changes of Aromatic Hydrophobic Regions

Abstract: Protein aggregation is a key concern in biopharmaceutical development and manufacturing. There is growing interest in understanding how the changes in protein microconformation affect the aggregation behavior. This study selected several representative proteins and first manipulated microconformational changes of the aromatic hydrophobic regions of proteins, especially tryptophan residues, by using amine or guanidine additives. The effects of the interactions between the additives and proteins on the aromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These non-covalent interactions (hydrogen bonding and charge–charge interactions), as well as the aromatic contacts, are typical of molecules able to bind amyloidogenic proteins, especially of amyloid inhibitors derived from natural products [ 73 75 ]. In this view, the interaction with Tyr169 may be significant by considering that it has been proposed how interactions can hamper the proteins aggregation process and protein misfolding [ 76 ], and suggested that aromatic interactions may be crucial in the aggregation process [ 77 ]. Moreover, it is worth noting that the Tyr169 is strictly conserved in mammalian PrPs likely implicated in the self-assembly process of E200K monomers through its involvement in stacking that are crucial for the formation of amyloid core [ 78 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These non-covalent interactions (hydrogen bonding and charge–charge interactions), as well as the aromatic contacts, are typical of molecules able to bind amyloidogenic proteins, especially of amyloid inhibitors derived from natural products [ 73 75 ]. In this view, the interaction with Tyr169 may be significant by considering that it has been proposed how interactions can hamper the proteins aggregation process and protein misfolding [ 76 ], and suggested that aromatic interactions may be crucial in the aggregation process [ 77 ]. Moreover, it is worth noting that the Tyr169 is strictly conserved in mammalian PrPs likely implicated in the self-assembly process of E200K monomers through its involvement in stacking that are crucial for the formation of amyloid core [ 78 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Fiber particles with large specic surface area were easily adsorbed by macromolecular protein aggregation, which result in particle size of protein-ber aggregate increasing quickly. 37 3.3. The varying tendency of the particle size distribution of whole cotyledon soymilk during the heating process…”
Section: The Varying Tendency Of the Volume Average Particle Size Andmentioning
confidence: 99%
“…When protein is exposed to a denaturing agent, the shift in its size to larger particles is commonly ascribed to random protein rearrangement into a looser structure and molecular aggregation [53] . Under harsh conditions, denaturation and protein unfolding may occur, followed by rapid and unspecific aggregation due to hydrophobic interactions among unfolded chains [55] . This effect occurs faster at higher concentrations of OSs, especially hydrophilic ones [31] .…”
Section: Resultsmentioning
confidence: 99%
“…[53] Under harsh conditions, denaturation and protein unfolding may occur, followed by rapid and unspecific aggregation due to hydrophobic interactions among unfolded chains. [55] This effect occurs faster at higher concentrations of OSs, especially hydrophilic ones. [31] In 40 % DMSO, after 5 h, the smallest HheC particles were about 700 nm in size (Figure 4C).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%